Deficits in Sagittal and Frontal Plane Mechanics during Drop Jump in Young Athletes with Recent Anterior Cruciate Ligament Reconstruction. Issue 7 (18th July 2016) - Pace, James Lee; Brophy, Christopher; Mueske, Nicole; Katzel, Mia; Healy, Bitte S.; Wren, Tishya
Objectives: While the vertical drop jump (VDJ) is an established predictor of ACL injury risk, most studies have focused on frontal and transverse plane assessment in young adult athletes. This study assessed sagittal as well as frontal plane biomechanics during VDJ in adolescent athletes following recent anterior cruciate ligament reconstruction (ACLR). Methods: 29 limbs with unilateral ACLR (69% female, mean age 15.8 ± 1.6 years, 5 to 12 months post-surgery), 29 contralateral non-operative limbs, and 19 control limbs (53% female, mean age of 15.5 ± 1.8 years) were evaluated during VDJ. Lower extremity three-dimensional kinematic and kinetic data from initial contact to peak knee flexion were compared among groups using analysis of variance with Bonferroni post-hoc tests. Results: The operative limbs had significantly lower peak ground reaction forces (GRF) than both control and contralateral limbs (ACLR: 1.7 body weights (BW), Contralateral: 2.1 BW, Control: 2.1 BW; p≤0.01) along with lower average external knee flexion moments (ACLR: 0.7Nm/kg, Contralateral: 0.9Nm/kg, Control: 1.1Nm/kg; p≤0.05) and reduced power absorption at the knee (ACLR: 0.9Nm/kg, Contralateral: 1.5Nm/kg, Control: 1.2Nm/kg; p≤0.01). Operative limbs had lower peak knee flexion (ACLR: 96.8°; Contralateral: 100.7°; p=0.001) and knee flexion excursion (ACLR: 75.0°, Contralateral: 82.5°; p=0.003) than contralateral limbs, but did not differ from controls in these measures. Both operative and non-operative limbs had greater peak hip flexion (ACLR: 98.9°, Contralateral: 99.8°, Control: 83.5°; p≤0.006), hip flexion excursion (ACLR: 60.8°, Contralateral: 65.6°, Control: 49.6°; p=), and power absorption at the hip (ACLR: 1.0Nm/kg, Contralateral: 1.2Nm/kg, Control: 0.7Nm/kg; p<0.03) compared with controls. In the coronal plane, both the operative and non-operative limbs demonstrated higher peak knee valgus moments compared to controls (ACLR: 0.5Nm/kg, Contralateral: 0.4Nm/kg, Control: 0.2Nm/kg; p≤0.02) and utilized less hip ab/adduction range (ACLR: 1.7°, Contralateral: 1.9°, Control: 6.1°; p≤0.003) though there were no differences in knee valgus angles (p≥0.31) or excursion (p≥0.52). Conclusion: Lower GRF and less energy absorbed at the knee during VDJ suggests a landing strategy that shifts loading from the post-surgical knee to the hip and contralateral limb. The frontal plane knee deficits in both the operative and non-operative limbs may place the limb at an elevated risk for future injury or re-injury. Avoidance of loading the reconstructed knee and residual deficits in frontal plane hip and knee control on either limb may indicate lack of readiness to return to full activity after recent ACLR.